Optical biosensors prospective based on Bragg grating polymer waveguide - Mohd Salleh, Mohd Hazimin; Mohd Salleh, Mohd Haziq; Abdul Hadi, Muhammad Salihi; , (Universiti Teknologi Malaysia, 2016)

(untitled)
In this work, we demonstrate the potential of Bragg grating polymer waveguide as an optical biosensor. Visible wavelength region at 650 nm is used as a centre wavelength because it is commonly used in biological and chemical sensing for both label and label-free sensing. The Bragg polymer waveguide structure is simulated using RSoft optical design and analysis software. The results show that there is a transmission drop with a 3 dB bandwidth of 661.0 nm when the surrounding refractive index is 1.33. The specific wavelength (transmission drop) is shifted to 724.2 nm when we increased the surrounding medium into 1.43 to mimic the bioanalytes solution. Simulation result shows that the wavelength shift was approximately 63.2 nm for every 0.1 increasing of surrounding refractive index. The Bragg grating polymer waveguide was fabricated by using electron beam lithography. Then, the fabricated devices were easily integrated within microfluidic systems in order to validate the wavelength shift. From the experiments, the wavelength shift occurred approximately 20.3 nm over 0.1 increment of refractive index. The discrepancies were likely due to the accumulation of sucrose solution on top and sidewall of the sensing area, the insertion loss between input and output coupling of the waveguide interface that induced the noise to signal ratio. Where we know that, is impossible to happen in simulation. Thus both simulation and experimental results strongly indicate that Bragg grating polymer waveguide structure at visible wavelength region have a potential for label or label-free optical biosensing applications